Mild microwave activated, chemo-thermal combinational tumor therapy based on a targeted, thermal-sensitive and magnetic micelle. (July 2017) - Li, Wei-Shuo; Wang, Xiao-Juan; Zhang, Shuo; Hu, Jing-Bo; Du, Yang-Long; Kang, Xu-Qi; Xu, Xiao-Ling; Ying, Xiao-Ying; You, Jian; Du, Yong-Zhong
Abstract: The development of combinational anti-tumor therapy is of great value. Here, the thermal-sensitive and hepatic tumor cell targeting peptide-A54 modified polymer, A54-poly(ethylene glycol)-g-poly(acrylamide-co-acrylonitrile) (A54-PEG-g-p(AAm-co-AN)) can self-assemble into an 80 nm-sized micelle, which shows a thermal-sensitive behavior with an upper critical solution temperature (UCST) of 43 °C. This self-assembled and targeted A54-PEG-g-p(AAm-co-AN) micelle can co-encapsulate anti-tumor drug doxorubicin (DOX) and magnetic nanoparticles (MNPs) taking advantage of the hydrophobic core of the core-shell micellar structure, when the temperature is lower than 43 °C. A much higher accumulation of the MNPs@A54-PEG-g-p(AAm-co-AN) to the tumor navigated by the A54 targeting peptide is achieved. Due to the thermal-agent effect of the accumulated MNPs in tumor, the mild microwave (8 W) applied afterwards specifically elevates the local tumor temperature by 13 °C, compared to 6 °C without MNPs accumulation in 30 min. The greater temperature rise resulted from the thermal-agent effect of MNPs doesn't only activate the drug release inside tumor cells, but also achieve an augmented hyperthermia. A mild microwave activated, chemo-thermal combinational tumor therapy is thus developed. Graphical abstract: